Kedudukan Majelis Penyelesaian Sengketa Pemilihan Kepala Desa - Sani, Ahmad Irfan (Jurnal Jatiswara, 2017)
This study aimed to analyze the Status of Assembly Resolution  Election Dispute village head (studies in western Sumbawa district). Issue law that emerged in this study include: How Assembly authority Dispute Resolution in the village election dispute resolution village elections in West Sumbawa regency  and What is the nature and the nature and implications of the decision of the Assembly  Settlement of the implementation of village elections  village elections in West Sumbawa regency. This research is a normative under consideration that this study departs from the analysis of the regulations legislation that describes the legal aspects related The position of the Assembly on Electoral Dispute Settlement village head. The approach used is a regulatory approach legislation, the conceptual approach and the approach to the case. Technics collection of legal materials to the study of literature. After that legal materials processing performed by holding systematization then do reasoning logically and systematically with descriptive qualitative analysis and draw conclusions in a manner deductive. Based on the results of this study concluded that based It can be concluded,that the authority of the Assembly Dispute settlement in the settlement village election dispute over village elections in West Sumbawa regency true West Sumbawa Regent is the authority granted by Article 37 paragraph (6) of Law No. 6 of 2014 on the village through Attribution in order to dispute election results village. The authority delegated by the Regent of West Sumbawa to Village Head Election Committee of the Regional level (PPKD District) through The mandate and the authority delegated back by PPKD District the MPS Pilkades through Sub Mandate. Shape and the nature and Settlement implications of the verdict of the village election  on the implementation of village elections in Sumbawa West, namely: the shape is the decision of the panel. Disposals rightly said final and binding. The implications socially verdict  political and able to repair a harmonious relationship